Avaliação do custo e equivalência farmacêutica de hidroclorotiazida em formulações industrializadas e magistrais - Gotardelo, Daniel Riani (2006)
The hydrochlorothiazide is one of the medicaments more prescribed in the treatment of the arterial hypertension all over the world. It has been used extensively in Brazil, in public program of Ministry of Health. Tests of pharmaceutical equivalence were accomplished in industrialized tablets and manipulated capsules seeking the verification of the quality and of the costs of the medicaments containing this drug. The dosage (determination of the tenor) was done by chromatography liquid of high efficiency, showing accuracy and specificity. Among the three industrialized medicines (generic, similar and reference), the generic medicament, although it is more than 40% cheaper in relation to the reference, it showed alterations in the test of hardness, indicating smaller resistance of that sample to the packing processes, storage and transport. Among the six coming lots of manipulation drugstores, one of the lots, that with the smallest cost of the market, showed dissolution in two times unsatisfactory, not having been approved in the initial evaluation done in all the lots of studied medicaments.